The Oxytocin–Vasopressin Pathway in the Context of Love and Fear - Carter, C. Sue (Frontiers in Endocrinology, 2017)
Vasopressin (VP) and oxytocin (OT) are distinct molecules; these peptides and their receptors (OTR and V1aR) also are evolved components of an integrated and adaptive system, here described as the OT-VP pathway. The more ancient peptide, VP and the V1aRs support individual survival and play a role in defensive behaviors, including mobilization and aggression. OT and OT receptors have been associated with positive social behaviors and may function as a biological metaphor for social attachment or “love.” However, complex behavioral functions, including selective sexual behaviors, social bonds and parenting required combined activities of OT and VP. The behavioral effects of OT and VP vary depending on perceived emotional context and the history of the individual. Paradoxical or contextual actions of OT also may reflect differential interactions with the OTR and V1aR. Adding to the complexity of this pathway is the fact that OT and VP receptors are variable, across species and individuals, and capable of being epigenetically tuned. This variation may help to explain experience-related individual and sex differences in behaviors that are regulated by these peptides, including the capacity to form social attachments and the emotional consequences of these attachments.